SOEHARTO lengser : perspektif luar negeri / Ben Anderson...[et al] ; penerjemah, Farid Wardiyono ; penyunting, Imam Baehaqi. - Anderson, Ben; Farid Wahdiyono; Imam Baehaqi (LKiS, 1998)
xv, 182 hlm. : ilus. ; 18 cm (3 eks.)